Nawazil Jurisprudence As a Source on the Islamic World: The Case of Al-Ajwibah Al-Kubra By: Abdelkader Al-Fassi - Klaina, Mekki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research examines Nawazil books as a vital indirect source for insights into Islamic societies across specific historical periods. Originally intended to provide legal rulings, these texts reveal the political, social, and economic conditions of their times. The study emphasizes the significance of Nawazil works, particularly from Andalusia and Morocco, offering a unique perspective on daily life and socio-economic interactions often missing from direct historical sources. The main goal is to assess how these rulings can aid in reconstructing historical contexts beyond their religious functions. The research problem addresses the extraction of historical facts from texts initially designed for legal judgments. Utilizing a historical and descriptive-analytical approach, the study explores texts like al-Ajwiba al-Kubra by al-Fassi Abdelkader. Findings show that Nawazil books provide valuable, often overlooked, details that can supplement traditional historical sources with intricate accounts of local realities.